What Makes Interactive Art Engaging? - Krzyzaniak, Michael; Erdem, Çağri; Glette, Kyrre (Frontiers in Computer Science, 2022)
Interactive art requires people to engage with it, and some works of interactive art are more intrinsically engaging than others. This article asks what properties of a work of interactive art promote engagement. More specifically, it examines four properties: (1) the number of controllable parameters in the interaction, (2) the use of fantasy in the work, (3) the timescale on which the work responds, and (4) the amount agency ascribed to the work. Each of these is hypothesized to promote engagement, and each hypothesis is tested with a controlled user study in an ecologically valid setting on the Internet. In these studies, we found that more controllable parameters increases engagement; the use of fantasy increases engagement for some users and not others; the timescale surprisingly has no significant on engagement but may relate to the style of interaction; and more ascribed agency is correlated with greater engagement although the direction of causation is not known. This is not intended to be an exhaustive list of all properties that may promote engagement, but rather a starting point for more studies of this kind.